2014
DOI: 10.3390/en7128411
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modeling of Ethanol Batch Fermentation by Escherichia Coli FBWHR Using Hot-Water Sugar Maple Wood Extract Hydrolyzate as Substrate

Abstract: A recombinant strain of Escherichia coli FBWHR was used for ethanol fermentation from hot-water sugar maple wood extract hydrolyzate in batch experiments. Kinetic studies of cell growth, sugar utilization and ethanol production were investigated at different initial total sugar concentrations of wood extract hydrolyzate. The highest ethanol concentration of 24.05 g/L was obtained using an initial total sugar concentration of 70.30 g/L. Unstructured models were developed to describe cell growth, sugar utilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…After hemicellulose and cellulose hydrolysis, a high concentration of hexoses and pentoses sugars can be obtained and subsequently fermented to produce different molecules such as organic acids or biofuels such as bioethanol. Bacteria such as Escherichia coli can metabolize hexoses and pentoses efficiently and to grow, in the presence or absence of oxygen, in minimum media without the addition of complex components . In addition, E. coli has been genetically modified to produce ethanol as the main product of fermentation and it has been demonstrated that ethanologenic E. coli strains can tolerate diverse toxic compounds present in lignocellulosic hydrolysates , including acetate …”
Section: Introductionmentioning
confidence: 99%
“…After hemicellulose and cellulose hydrolysis, a high concentration of hexoses and pentoses sugars can be obtained and subsequently fermented to produce different molecules such as organic acids or biofuels such as bioethanol. Bacteria such as Escherichia coli can metabolize hexoses and pentoses efficiently and to grow, in the presence or absence of oxygen, in minimum media without the addition of complex components . In addition, E. coli has been genetically modified to produce ethanol as the main product of fermentation and it has been demonstrated that ethanologenic E. coli strains can tolerate diverse toxic compounds present in lignocellulosic hydrolysates , including acetate …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, effect of these inhibitors on ethanol yield and productivity must be studied for commercialization of lignocellulosic ethanol process. (Nichols et al 2008;Pampulha and Loureiro-Das 2000;Abbott and Ingledew 2004;Graves et al 2000;Wang and Liu 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays alternate form of energy production, chemicals and fuels are being focused due to scarcity and high prices of available natural resources [1][2][3]. Biomass can be used as source of raw material to fulfill ongoing demand of fuel.…”
Section: Introductionmentioning
confidence: 99%